RANCANG BANGUN TELEMONITORING OXIMETRY, ECG, DAN TEMPERATURE NIRKABEL - Wiratama, Andika Ryan; Ardyana, Yugi; Al Biruni, Muhammad Raihan; Supartha, Dewa Ayu Githa Maharani; Meilisa, Fransiska (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Lack of medical personnel in Indonesia led to many patients who need intensive care and their conditions are not monitored in real time as well as patientsâs room with the doctors office away from each other. So this activity aims to facilitate monitoring of blood oxygen saturation levels,Â cardiac signal and temperature of the patient even though the doctor is not in place. ECG circuits that is made had HPF circuit wich pass frequencies above 0.05 Hz, LPF circuits which pass frequencies below 100 Hz, and Notcoh filter circuit that can eliminate the grid. At oximetry sensor circuit built using red LED (Light Emitting Diode) and infrared LED. In the temperature circuits,Â IC LM-35 is used as a temperature sensor. All three circuits were combined with a microcontroller to a PC and Â processed by a program has been designed and accepted by smartphones. The results that have been obtained from the test on each parameter there are no real difference to the oximetry, ECG, and temperature calibrator tool.Key Words: ECG, Oximetry, temperature.